Retrolental fibroplasias: What lies beneath? - Sen, Parveen; Shah, Dhaivat (GMS Ophthalmology Cases, 2020)
A nine-month-old female baby with normal birth history presented with her mother complaining of a white spot in the baby’s right eye, which the mother had noticed at five months of age. External photograph showed a retrolental fibroplastic membrane visible in the superior half of the dilated pupil. Retcam fundus photo revealed myelinated nerve fibers extending from the disc till the ora superiorly and forming a membranous fold. Intraoperative OCT confirmed thickened RNFL with compact retina. Thus, the retrolental fibroplasia turned out to be a masquerade for myelinated nerve fibers. Since it was not involving the visual axis with no coexisting traction, the mother was reassured regarding the benign nature of the condition.